The pass-through of gaps between market rent and the price of shelter - Christopher D. Cotton (Federal Reserve Bank of Boston, 2024)
The gap between market rent and the price of shelter was 6.6 percent larger in December 2023 relative to December 2019. Because shelter prices comprise 36 percent of the Consumer Price Index and therefore influence monetary policy decisions, it is vital to understand the pass-through of this difference, or "market-shelter gap." I use MSA-level variation to answer this question. When there is a positive market-shelter gap, the price of shelter grows faster and market rent grows slower until the gap closes, which takes about five years. Faster shelter-price growth and slower market-rent growth each explain about half of the convergence.
Keywords: E37; E31; E17; 330; CPI; shelter; housing; rent; market-shelter gap